Safe Embrace: technological innovation for elderly safety in the use of toilets - Luciana Mitsue Sakano Niwa; Nanci Martins Ferreira Radovich; Suely Itsuko Ciosak
ABSTRACT Objective: to describe the development of a device to prevent falling for seniors when using the toilet. Method: we sought in literature and in the hospital market for a device to prevent falling, without success. Geriatric nurses, in partnership with the hospital engineering team, elaborated a prototype and, after several analysis, looked for a partner for its production. Results: the device, named "Safe Embrace", installed and tested in an apartment of the Geriatric ward, was positively evaluated by the health team, patients and caregivers. Conclusion: for the benefit obtained and considering the safety and privacy during use, Safe Embrace was patented so that other institutions could use it.